2013
DOI: 10.1002/ana.23867
|View full text |Cite
|
Sign up to set email alerts
|

Pathological correlates of magnetic resonance imaging texture heterogeneity in multiple sclerosis

Abstract: Texture analysis performed on routine clinical magnetic resonance images may be a potential measure of tissue integrity. Tissues with more severe myelin and axonal pathology are associated with greater texture heterogeneity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 37 publications
(52 reference statements)
6
56
0
Order By: Relevance
“…In vivo mapping of myelin density15 and g‐ratio16; iron deposition17; sodium concentration18; inflammation and axonal injury19 are examples of quantitative MRI techniques being developed to detect early multiple sclerosis pathology. Similar quantitative MRI metrics require extensive validation, in order to confirm their specificity and relevance to clinical outcomes 20, 21, 22…”
Section: Introductionmentioning
confidence: 99%
“…In vivo mapping of myelin density15 and g‐ratio16; iron deposition17; sodium concentration18; inflammation and axonal injury19 are examples of quantitative MRI techniques being developed to detect early multiple sclerosis pathology. Similar quantitative MRI metrics require extensive validation, in order to confirm their specificity and relevance to clinical outcomes 20, 21, 22…”
Section: Introductionmentioning
confidence: 99%
“…Although, to the best of our knowledge, there are no studies correlating in vivo texture measures with histopathology, Zhang et al 31 performed a study in which they found correlation among histopathology and texture parameters obtained from MR imaging of postmortem tissue samples of patients with multiple sclerosis. Possible tissue changes in the medulla oblongata are in line with previous pathologic reports in FA.…”
Section: Discussionmentioning
confidence: 99%
“…Using standard MR images, texture analysis demonstrates the ability to differentiate normal from abnormal MS tissue, and to distinguish active from inactive MS lesions in the brain [9][10][11] . Recently, using a new local spatial frequency-based algorithm [12][13][14] , MRI texture analysis detected differences of demyelination, axonal injury and inflammation between focal and diffuse MS abnormalities in fixed postmortem brain samples 15 . In the current study, we adapted this localized texture analysis method to determine whether different types of MS lesions…”
Section: Zhang Et Almentioning
confidence: 99%
“…The signal intensity patterns of T2-weighted MRI were evaluated using a local spatial frequency-based program as reported previously 15 . In brief, the entire frequency content enclosed in the whole MR image was initially calculated using the classical Fourier transform; then, the spatial distribution of each frequency at individual spatial resolutions of the image was determined by applying the inverse Fourier transform.…”
Section: Mri Texture Analysismentioning
confidence: 99%
See 1 more Smart Citation